Conservative Treatment of a Patient with Epidermolysis Bullosa Presenting as Bart Syndrome: A Case Report - Samet Vasfi Kuvat; Mehmet Bozkurt (Case Reports in Medicine)
We presented a case of a newborn male with aplasia cutis congenita on the lower limb. The case was treated with conservative method. As for the conservative treatment, daily hydrodebridement with 1/200 diluted povidone-iodine and serum physiologic was performed, followed by closure of the wound with a dexpanthenol + chlorhexidine + fusidic acid-impregnated sterile gauze bandage. the followup that occured after three weeks, the wound was completely epithelialized, but a hypopigmented scar remained in the limb.